Teaching braille letters, numerals, punctuation, and contractions to sighted individuals. Issue 2 (5th May 2015) - Putnam, Brittany C.; Tiger, Jeffrey H.
<x xml:space="preserve">Abstract</x> Braille‐character recognition is one of the foundational skills required for teachers of braille. Prior research has evaluated computer programming for teaching braille‐to‐print letter relations (e.g., Scheithauer & Tiger, 2012). In the current study, we developed a program (the Visual Braille Trainer) to teach not only letters but also numerals, punctuation, symbols, and contractions; we evaluated this program with 4 sighted undergraduate participants. Exposure to this program resulted in mastery of all braille‐to‐print relations for each participant.